BIBLIOMETRICS ANALYSIS OF DIGITAL LEADERSHIP RESEARCH - Purwanto, Edi; Irawan, Agustinus Purna (International Journal of Application on Economics and Business, 2023)
This paper presents a comprehensive analysis of digital leadership research using bibliometric analysis and network visualization techniques. The study utilizes bibliometrics to gain insights and comprehend patterns in scientific publications related to digital leadership. Data from various sources, including articles, conference papers, and book chapters in the Scopus database, was analyzed using mathematical and statistical methods. The search term "digital leadership" resulted in 127 relevant publications from Scopus.com. Through bibliometric parameters such as authors, citations, keywords, and publication countries, the study offers a systematic research method for thematic analyses. The findings from this research provide researchers with specific inquiries and recommended considerations at each stage of the bibliometric analysis process. The study sheds light on the trends and developments in digital leadership research, identifying potential research gaps and opportunities for future investigations. By utilizing robust research methodologies, this paper contributes to understanding digital leadership and informs scholars on the key themes shaping the field's trajectory.